REDUCTION OF MERCURY CONTENT IN LIQUID MEDIA BY ADSORPTION PROCESS USING COAL FLY ASH - Doni Rahmat Wicakso; Maya Puspita Sari; Ni Luh Ratna A. K. D. (Universitas Lambung Mangkurat, 2020)
Industrial and technological advancements have been able to improve the welfare of humanity, but present the consequences of environmental pollution which ultimately also affects human life. The well water used by residents as a necessity of life can be polluted due to gold mining because the gold mining is located not far from the residential area. The purpose of this study is to determine the levels of mercury in the liquid medium before and after the adsorption process, determine the ability of coal fly ash as an adsorbent in absorbing mercury in the liquid medium and determine the optimum contact times in mass variations of coal fly ash.Activation of coal fly ash was done by calcination for 2 hours, followed by measurement of initial concentration for liquid medium, the adsorption process is carried out with a coal fly ash mass variation of 4, 6, 8 and 10 g, and variations of adsorption time that is 10, 20, 30, 40 and 50 minutes. From the results of the study, obtained levels of mercury in the liquid medium before the adsorption process was carried out at 0.3263 ppm and after the adsorption process ranged from 0.2053 to 0.3023 ppm. Thus, coal fly ash has a low absorption ability to mercury in liquid medium and the best contact time where adsorption occurs for a mass of 6 g is at 10 minutes which is equal to 0.1210 ppm.